2021
DOI: 10.3389/fnbeh.2021.634158
|View full text |Cite
|
Sign up to set email alerts
|

Paper Notebooks vs. Mobile Devices: Brain Activation Differences During Memory Retrieval

Abstract: It remains to be determined how different inputs for memory-encoding, such as the use of paper notebooks or mobile devices, affect retrieval processes. We compared three groups of participants who read dialogues on personal schedules and wrote down the scheduled appointments on a calendar using a paper notebook (Note), an electronic tablet (Tablet), or a smartphone (Phone). After the retention period for an hour including an interference task, we tested recognition memory of those appointments with visually pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…They observed brain activation in the hippocampus and precuneus, which are related to memory function during the deeper encoding and retrieval of specific information. They found that the activation in these areas was stronger in groups using a paper notebook than in those using digital devices, 30 indicating that using paper notebooks promotes active brain function. Digital devices can also encode information equally to paper; however, it is inferior to paper in storing information.…”
Section: Discussionmentioning
confidence: 99%
“…They observed brain activation in the hippocampus and precuneus, which are related to memory function during the deeper encoding and retrieval of specific information. They found that the activation in these areas was stronger in groups using a paper notebook than in those using digital devices, 30 indicating that using paper notebooks promotes active brain function. Digital devices can also encode information equally to paper; however, it is inferior to paper in storing information.…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicated that accuracy in the retrieval was not significantly different among the three groups. On the other hand, the notebook learning group showed higher brain activity during the memory retrieval phases compared to the other groups [8]. Since task performances were similar among the three groups, higher brain activity in the notebook learning group could be considered using a greater amount of brain energy to produce the same level of results.…”
Section: Introductionmentioning
confidence: 85%
“…Although test performances did not significantly differ between the two groups, the digital tablet-based learning group showed higher brain activity while performing the task [1]. Furthermore, despite the fact that the stages of memory are divided into encoding and retrieval, and it has been shown that the brain offers different contributions in the encoding and retrieval phases [9][10][11], previous studies have not analyzed brain efficiency by learning media by stages, making it difficult to clearly identify at which stage there is a difference in brain efficiency [1,8] Consequently, there is ongoing debate regarding brain efficiency associated with learning through different media, and the question of how the brain efficiency of digital tablet-based learning differs from that of paper-based learning remains unclear. Furthermore, neither of the studies presented brain activity for the encoding and retrieval phases, leading to a challenge in pinpointing the specific phase where differences in brain efficiency occur.…”
Section: Introductionmentioning
confidence: 99%
“…Umejima et al [ 35 ] also investigated encoding and retrieval from reading in different media, using functional resonance imaging (fMRI). For the encoding phase, participants read appointment information in three conditions: paper notebooks, digital tablets, and mobile phones.…”
Section: Introductionmentioning
confidence: 99%